2018
DOI: 10.1080/15524256.2018.1437590
|View full text |Cite
|
Sign up to set email alerts
|

Social Workers’ Perceptions of Job Satisfaction, Interdisciplinary Collaboration, and Organizational Leadership

Abstract: To address job satisfaction, and therefore employment retention, of hospice social workers, this study examined how relationships with other members of the interdisciplinary hospice team and perceptions of hospice leadership may be associated with job satisfaction of hospice social workers. The sample of 203 hospice social workers was recruited by e-mailing invitations to hospice social workers identified by hospice directors in three states, use of online social media sites accessed by hospice social workers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…As personal experiences with death, dying and bereavement influence professional care delivery, 46,114 social workers who have more of those experiences may be better equipped for palliative care practice. Furthermore, low job satisfaction has also been linked to a low understanding of the social work contribution among other professionals, 90 a general feeling of being disvalued in multidisciplinary practice 72,76 and the inability to put holistic social work values into practice due to various policy or organisational constraints. 49 How can this prerequisite be realised in practice?…”
Section: Clear Role Description and Set Of Core Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…As personal experiences with death, dying and bereavement influence professional care delivery, 46,114 social workers who have more of those experiences may be better equipped for palliative care practice. Furthermore, low job satisfaction has also been linked to a low understanding of the social work contribution among other professionals, 90 a general feeling of being disvalued in multidisciplinary practice 72,76 and the inability to put holistic social work values into practice due to various policy or organisational constraints. 49 How can this prerequisite be realised in practice?…”
Section: Clear Role Description and Set Of Core Competenciesmentioning
confidence: 99%
“…46,56,112,115,118 On the other hand, various organisations of employment -such as home care or hospice care services -should stimulate job satisfaction and provide self-care and coping strategies for their social workers. 72,76,113,116 Moreover, as the likelihood on job satisfaction of social workers is higher in organisations where holistic social work values can be put into practice, it is important to align the organisational culture with those values. 49 Peer support through social work networks or organised mentorship.…”
Section: Clear Role Description and Set Of Core Competenciesmentioning
confidence: 99%
“…But, there are specific gaps concerning the impact of behavioral genetics and decision making (Vroom, 2003) on various leadership styles. Though recent investigations (Marmo and Berkman, 2018; Paquin et al , 2018; Cardiff et al , 2018) have initiated critical inter-disciplinary interactions on leadership, still there are not enough studies to emphatically estimate the influence of leadership in the areas like neuromarketing, neuroimaging, organizational neuroscience, etc. Researchers could also focus on varied perspectives like reductionism, technology aid, experiences, etc., connecting divergent styles of leadership.…”
Section: Discussion: Broad Areas Of Future Researchmentioning
confidence: 99%
“…Transformational leadership by surgeons also has been associated with better team performance in the operating room (Hu et al, 2016). Marmo and Berkman (2018), in a study of 203 hospice social workers, found that the perception of servant leadership was related to higher job satisfaction. Other variables linked to job satisfaction were interdisciplinary collaboration and feeling valued by the hospice physician.…”
Section: Evidence On the Various Leadership Styles And Organizational Outcomesmentioning
confidence: 99%